Clinical Outcomes of Prosthetic Knee Joint Infection in a United States Tertiary Healthcare Center. (4th October 2017) - Ayoade, Folusakin; Todd, John
Abstract: Background: The 2013 IDSA prosthetic joint infection (PJI) guidelines identified some research gaps, some of which include what factors may predict PJI outcome. We therefore conducted a retrospective single-center study with the goal of addressing some of these gaps. Objectives: 1. Describe the incidence, pathogens, role of inflammatory markers, and treatment outcomes of knee PJI. 2. Identify correlations between joint aspiration (JA) and intraoperative (IO) cultures. Methods: We retrospectively analyzed all adult knee PJI that were diagnosed and managed at our institution between 1/1/2005 and 12/31/2015. Statistical analysis was done using the paired t -test, Fisher exact and McNemar χ 2 tests as applicable. Results: Forty-six subjects met the inclusion criteria and were analyzed. See table below. The incidence rate of PJI for the study period was 5.4%.. Staph. aureus was the commonest pathogen accounting for 11(65%) JA and 13(40%) of IO cultures. Low virulence organisms [ Staph. epidermidis n = 8 (25%) and Corynebacterium spp. n =1 (3%)] were only recovered from IO cultures. Gram-negative bacilli accounted for 5(30%) JA and 7(28%) IO cultures.. JA correlates well with IO cultures using paired sample correlations ( t -test); (correlation 0.61, P = 0.027).. 97% of subjects had elevated ESR while 96% had elevated CRP.. Concerning outcome, there was no statistically significant difference between groups based on implant duration ( P = 0.98), symptom onset ( P = 0.23), pathogen type ( P = 0.83), and treatment options ( P  = 0.39). Conclusion: 1. JA culture is a good predictor of IO culture in knee PJI. 2. Yield of low virulence organisms from JA culture is poor. 3. Elevated ESR and CRP can support diagnosis of knee PJI. 4. Implant duration, pathogen type, duration of symptoms and treatment type do not appear to affect outcome. Disclosures: All authors: No reported disclosures.